Stock market integration between new EU member states and the Euro-zone - Aslanidis, Nektarios; Savva, Christos S.; Aslanidis, Nektarios (My University, 2010)
This paper measures the degree in stock market integration between five Eastern European countries and the Euro-zone. A potentially gradual transition in correlations is accommodated by smooth transition conditional correlation models. We find that the Czech, Slovenian and Polish markets have increased their correlation to the Euro-zone from 1997 to 2008. However, this is not a broad-based phenomenon across Eastern Europe. The results also show that the increase in correlations is not a reflection of a world-wide phenomenon of financial integration but is mainly driven by EU-related developments.
Keywords: Multivariate GARCH; New EU members; Smooth transition conditional correlation; Stock return comovement; Multivariate GARCH; New EU members; Smooth transition conditional correlation; Stock return comovement